Influência da pressão pulpar simulada na variação de temperatura intrapulpar durante a fotopolimerização do sistema adesivo - Silva, Tânia Mara da [UNESP]; Gonçalves, Lucélia Lemes [UNESP]; Siqueira, Erika Priscila [UNESP]; Pereira, Tatiana Cursino [UNESP]; Pontes, Solimar de Oliveira [UNESP]; Grecca, Amanda Reis [UNESP]; Lopes, Stephanie Ribeiro [UNESP]; Gonçalves, Sérgio Eduardo de Paiva [UNESP] (Editora Cubo, 2017)
Objective: To evaluate the effects of simulated pulpal pressure (SPP) on the variation of intrapulpal temperature (⃞T) during lightcuring of the adhesive system. Material and Methods: One hundred sound human molars were sectioned from the highest pulp horn to obtain a 2-mm of thickness dentin. The specimens were randomly divided into two groups: (n = 50), according to the presence or absence of SPP (15 cm H2O). The specimens were sequentially treated as follows: 37% phosphoric acid (Scotchbond Universal; 3M/ESPE), adhesive system (Scotchbond Universal/3M ESPE) and light-curing (10 s). ⃞T was evaluated during adhesive lightcuring with a K-type thermometer put inside the pulp chamber. Data were analysed by using Mann-Whitney’s test (at 5%). Results: According to Mann-Whitney’s test, the absence group presented a ⃞T of 2 °C, whereas the presence group 1 °C. The mean values of ⃞T were 0.82 ± 0.56 °C for the presence group and 2.30±0.73 °C for the absence group. Conclusion: Simulated pulpal pressure significantly reduced the temperature rise in the pulp chamber during light-curing of the adhesive system, showing the importance of inserting this protocol of simulated pulpal pressure in the laboratory procedures.
Influence of simulated pulpal pressure on the variation of intrapulpal temperature during adhesive system light-curing
Keywords: Dentin; Light-curing; Pulpal pressure; Temperature